Isolated Liver Metastasis in Hürthle Cell Thyroid Cancer Treated with Microwave Ablation - Konstantinos Segkos; Carl Schmidt; Fadi Nabhan (Case Reports in Endocrinology)
Hürthle cell thyroid cancer (HCTC) is a less common form of differentiated thyroid cancer. It rarely metastasizes to the liver, and when it does, the metastasis is almost never isolated. Here we report a 62-year-old male with widely invasive Hürthle cell thyroid cancer, who underwent total thyroidectomy and received adjuvant treatment with I-131 with posttreatment scan showing no evidence of metastatic disease. His thyroglobulin however continued to rise after that and eventually an isolated liver metastasis was identified. He underwent laparoscopic microwave ablation of the liver metastasis, with dramatic decline in thyroglobulin and no structural disease identified to date. This case highlights the rare occurrence of isolated liver metastasis from HCTC and also illustrates the utility of thermoablation as an alternative to surgical resection in the treatment of small isolated liver metastases from HCTC.